Cost and management accounting : an introduction - Drury, Colin. 4 0 16; 5 (Australia ;;United States : Thomson, 2006)
An introductory textbook on management accounting featuring learning objectives, examples, key term and concept lists, important examination points, review problems with answers, and a summary in each chapter.
Cover title: Cost & management accounting.
Includes bibliographical references (p. 541-543) and index.
Adult;Adult
Keywords: 2 -- 0; 6; Managerial accounting.;Cost accounting.;Managerial accounting.;Cost accounting; 20; 2